Recycling of non-metallic residue from waste printed circuit boards to produce interlocking concrete blocks - Sawitri Pianchaiyaphum (2022)
The process of copper recovery from waste printed circuit board has generated large amounts of non-metallic fraction (NMF) residue. In this research, the residue was recycled as a substitute for fine aggregates at 0%, 5%, 10%, 15%, and 20% to produce interlocking concrete blocks. Properties of the interlocking concrete blocks produced in this study, such as density, water absorption, compressive strength, were firstly examined and the selected mixes were further evaluated for the heavy metal leachability. The results indicated that the NMF residue affected physical, mechanical and chemical properties of NMF interlocking concrete block samples. When increasing NMF contents, the density and compressive strength decreased, while the water absorption increased. In the leachability results, the leaching of Cu decreased as cement content increased, and its concentration level was well below the Soluble Threshold Limit Concentration limit (STLC). Thus, the high content of Cu and all other metals embedded in the NMF material were immobilized in the interlocking concrete block specimens.